2013
DOI: 10.1111/sum.12047
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and desorption of phosphate on biochar and biochar–soil mixtures

Abstract: The term biochar refers to materials with diverse chemical, physical and physicochemical characteristics that have potential as a soil amendment. The purpose of this study was to investigate the P sorption/desorption properties of various slow biochars and one fast pyrolysis biochar and to determine how a fast pyrolysis biochar influences these properties in a degraded tropical soil. The fast pyrolysis biochar was a mixture of three separate biochars: sawdust, elephant grass and sugar cane leaves. Three other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(50 citation statements)
references
References 27 publications
1
47
0
2
Order By: Relevance
“…A previous study indicated that 100% sorption efficiency could be achieved by GC beds designed with 2-4 mm particle size and a contact time of 24 h. [31] Biochar, on the other hand, is said to be capable of 100% sorption efficiency if particle size ≤2 mm and a contact time of 72 h are used. [43] However, the GC and C material used in this study had large particle size and short contact times. These may have been the cause of the unexpectedly lower efficiency.…”
Section: Phosphorus Removal Efficiencymentioning
confidence: 96%
“…A previous study indicated that 100% sorption efficiency could be achieved by GC beds designed with 2-4 mm particle size and a contact time of 24 h. [31] Biochar, on the other hand, is said to be capable of 100% sorption efficiency if particle size ≤2 mm and a contact time of 72 h are used. [43] However, the GC and C material used in this study had large particle size and short contact times. These may have been the cause of the unexpectedly lower efficiency.…”
Section: Phosphorus Removal Efficiencymentioning
confidence: 96%
“…Furthermore, both NH + 4 adsorption by up to 15 % from aqueous solution and leaching by up to 4 % into solution were observed (Yao et al, 2012). Other nutrients which are not particularly prone to leaching, such as PO 3− 4 , have also been reported to be retained by application of pyrochar (Laird et al, 2010;Morales et al, 2013;Xu et al, 2014). For example, Laird et al (2010) reported up to 70 % reduced PO 3− 4 -P leaching in a soil column experiment mixed with 20 g kg −1 pyrochar.…”
mentioning
confidence: 97%
“…In summary, according to the majority of studies (Hale et al, 2013;Knowles et al, 2011;Lehmann et al, 2003;Morales et al, 2013;Xu et al, 2014), char may be a potential melioration for soils by decreasing nutrient leaching via improved adsorption properties. However, there is only little knowledge on the nutrient sorption potential of pyrochars compared to hydrochars, and the influence of aging/degradation on nutrient sorption.…”
mentioning
confidence: 98%
“…It is a porous material with high surface area (Dias et al 2010), thus it can significantly affect soil moisture and reduce the loss of nutrients. Even biochar itself can release some N, P and K and can be applied for the supply of nutrients from biochar to soil and plant (Angst and Sohi 2013;Guerena et al 2013;Morales 2013;Mukherjee and Zimmerman 2013). Biochar has a higher capacity for cation adsorption per unit carbon than other soil organic matters (Silber et al 2010) due to its greater surface area, greater negative surface charge, and greater charge density, which can be even enhanced through some geochemical weathering process (Yao et al 2010).…”
Section: Introductionmentioning
confidence: 99%